CRITICAL MINDFULNESS IN THE SECONDARY ENGLISH LANGUAGE ARTS CLASSROOM - (:unkn) unknown (My University, 2024)
This qualitative dissertation examines teachers’ perceptions of integrating mindfulness practices in secondary English Language Arts (ELA) classrooms, emphasizing urban schools with a significant number of Black and Brown students. The study addresses the gap in existing research examining if mindfulness is aligned with culturally-based pedagogies to support Black and Brown students effectively. The central research question is: What frameworks do ELA teachers use to deliver mindfulness within the curriculum and pedagogy to support Black and Brown students in urban secondary settings? Using a phenomenological intuitive inquiry research design, this research analyzed interviews of seven secondary ELA teachers across five cycles of analysis. The findings reveal the nuances of various mindfulness applications in the ELA classroom. Key themes emerged, such as the use of mindfulness to enhance social- emotional learning (SEL), and its impact on student well-being by providing strategies to manage stress and emotions. Teachers perceived improvements in student engagement, and a decrease in disruptive behavior attributed to mindfulness. In the final analysis cycle of the teachers’ interviews, two lenses were identified: the (in)visibility of white supremacy in mindfulness instruction and cultivating consciousness: the gap in culturally relevant mindfulness. Findings suggest teachers perceive mindfulness as a tool to enhance student achievement and well-being, but the implementation often lacked cultural-based frameworks, thus not fully supporting students. Instead, mindfulness was primarily used as a classroom management tool rather than leveraging its full potential. Additionally, findings show these teachers used deficit language that reinforced systemic biases by ignoring the socio-political factors that impact students experiences and needs. Further, the teachers in the study did not make any culturally relevant adaptations to the mindfulness curriculum and instead relied on generalized programs devoid of an acknowledgment of the unique cultures of Black and Brown students. This study emphasizes the need for an anti-oppressive framework that is culturally-based explicitly in the mindfulness curriculum. The implications of this study suggest that for mindfulness to positively impact Black and Brown students in secondary ELA settings, it must go beyond generalizable applications and be deeply ingrained with culturally-based teaching pedagogies.